Pengaruh Kombinasi Relaksasi Benson dan Posisi Fowler terhadap Frekuensi Nafas pada Pasien Asma - Eka Putri Angelyta; Indah Sri Wahyuningsih; Retno Setyawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Asthma is a chronic disease that can cause respiratory problems and affect a patient's quality of life. One of the most common symptoms of asthma is increased respiratory rate. The combination of the Benson and Fowler positions has been shown to be effective in reducing stress and increasing lung capacity. The purpose of this study was to determine the effect of the Benson and Fowler positions on respiratory rate in asthma patients. This was a descriptive observational study. The sample used in this study was 18 respondents. Data collection was carried out using a respiratory frequency observation sheet. The data obtained were statistically processed using the Wilcoxon test formula. The characteristics of asthma patient respondents at Sultan Agung Islamic Hospital, Semarang, were predominantly female (11 respondents (61.1%), predominantly aged 8 respondents (44.4%) and 46-55 years old (12 respondents (66.7%), predominantly employed as laborers (12 respondents (66.7%), predominantly educated as high school (9 respondents (50.0%), predominantly diagnosed as allergic asthma (11 respondents (61.1%), and predominantly underwent therapy for more than 6 months (16 respondents (88.9%). The mean respiratory rate (RR) in asthma patients before the intervention was 24.78 ± 1.263. The mean respiratory rate (RR) in asthma patients after the intervention was 19.50 ± 2.121). There is a combination of Benson and Fowler positions on respiratory rate in asthma patients at Sultan Agung Islamic Hospital, Semarang (p-value < 0.05).